Professional ethics, VBAC and COVID-19 pandemic: A challenge to be resolved (Review) - Carauleanu, Alexandru (Exp Ther Med, 2021)
Since the declaration of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic by the World Health Organization (WHO) on March 11, 2020, the entire healthcare system is trying to adapt its capabilities to a challenge that induces a deep and continuous metamorphosis of people, strategies and policies. The right to proper health care is universal, and the patient's autonomy must be respected even in ambiguous times. In the context of increased Cesarean section (CS) rates, the women's desire to achieve vaginal birth after Cesarean section (VBAC) is becoming more articulate, and healthcare professionals need to adapt their approaches regarding the mode of delivery. But how to balance this aspect with respect to the paucity of resources during the pandemic, without infringing the fundamental rights and ethical principles is a demanding question. This article describes a clinical ethical decision-making framework for recommending trial of labor after Cesarean section (TOLAC), and individualized management of VBAC cases tailored upon the new circumstances dictated by the SARS-CoV-2 pandemic.